Relationship between Knowledge, Perception, and Self-Efficacy of Junior High School Students towards HPV Vaccination as Cervical Cancer Prevention in Surakarta - Khansa Nuriashinta Nabila; Yuli Kusumawati (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Cervical cancer remains a major health concern for women in Indonesia, including Surakarta, where participation in HPV screening and vaccination is still low. Objective: This study aimed to examine the relationship between knowledge, perception, and self-efficacy regarding HPV vaccination among junior high school girls in Surakarta. Methods: A cross-sectional study was conducted among 200 students from four randomly selected junior high schools using cluster sampling, with data analyzed using the Spearman Rho correlation test. Results: More than half of the students (52.6%) demonstrated poor knowledge about cervical cancer and the HPV vaccine, yet the majority exhibited high self-efficacy toward vaccination. The analysis revealed no significant relationship between knowledge and self-efficacy (p = 0.589), but a significant, albeit weak, correlation was found between knowledge and perception (p = 0.036; r = 0.15). These findings indicate that improved knowledge contributes to more positive perceptions of HPV vaccination, though self-efficacy tends to be shaped by personal motivation and external support such as parental or peer encouragement. Conclusion: Strengthening health education programs through schools and families is essential to enhance awareness, correct misconceptions, and foster stronger motivation among adolescent girls to participate in HPV vaccination as a preventive strategy against cervical cancer.